1998
DOI: 10.1046/j.1523-1755.1998.00971.x
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of developing metanephroi into adult rats

Abstract: Our findings establish that functional chimeric kidneys develop from metanephroi transplanted in adult hosts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
224
2
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(242 citation statements)
references
References 20 publications
15
224
2
1
Order By: Relevance
“…Previous studies described the direct connection of a recipient ureter with the ureter of a transplant-grown metanephros (uretero-ureterostomy) to create a urine excretion channel for a neokidney (Fig. S1B) (11)(12)(13), prolonging the short-term survival of anephric rats (12,13). However, our SWPU system is more efficient than previous methods in many ways.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies described the direct connection of a recipient ureter with the ureter of a transplant-grown metanephros (uretero-ureterostomy) to create a urine excretion channel for a neokidney (Fig. S1B) (11)(12)(13), prolonging the short-term survival of anephric rats (12,13). However, our SWPU system is more efficient than previous methods in many ways.…”
Section: Discussionmentioning
confidence: 95%
“…Metanephroi and cloacas were implanted in the omenta of anesthetized host animals ( Fig. S5) as previously reported (10,11,19).…”
mentioning
confidence: 99%
“…4 Although FHH could largely be accounted for by a reset of the parathyroid calciostat, studies by Attie et al demonstrated that unusually low calcium clearance seen in FHH patients was caused by abnormal calcium sensing by the ascending limb of Henle's loop, in a fashion that was independent of systemic changes in PTH. 5 Subsequent to the cloning of the CaSR from parathyroid glands, the receptor was also identified from the rat kidney, 6 with the highest expression at the basolateral membrane of thick ascending limb cells and, to a lesser extent, in proximal convoluted tubules and collecting ducts. 7 Functional studies in isolated nephron segments and kidney-derived cell lines suggest that the renal CaSR is involved in mineral ion homeostasis, regulation of urine acidification, concentration, and of renin secretion (reviewed by Riccardi and Brown 8 ).…”
Section: Disclosuresmentioning
confidence: 99%
“…Several experimental attempts to "grow" new kidney tissue into animal hosts have shown that intact fetal kidneys or fragments become vascularized by the recipient, undergo morphologic maturation, and may exhibit functional properties. [6][7][8][9][10][11][12] For example, whole metanephroi transplanted into nonimmunosuppressed hosts are successfully vascularized by host arteries, form mature nephrons, and are not rejected. 6 Fetal kidneys maintained in culture become vascularized and form normal glomeruli when grafted into the eye chamber of adult host mice.…”
mentioning
confidence: 99%
See 1 more Smart Citation